(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The article deals with the main formation sources of poetic outlook of V. Yaroshenko. The main forms of expression of the author’s mind and originality of imagery system of poetic means of V. Yaroshenko as a symbolist were determined. The philosophical and aesthetic concept of V. Yaroshenko and his appealing to the problem of alienation of personality were analyzed.